3D printing of pink bioceramic scaffolds for bone tumor tissue therapy. (June 2022) - Wang, Xin; Zhai, Dong; Yao, Xiaogang; Wang, Yufeng; Ma, Hongshi; Yu, Xiaopeng; Du, Lin; Lin, Huixing; Wu, Chengtie
Highlights: Pink CaTiO3 bioceramic scaffolds were fabricated via digital laser processing (DLP) based 3D printing technology. After sintered at high temperature, CaTiO3 bioceramic scaffolds exhibited improved compressive strength and satisfactory photothermal property. 3D printed bifunctional CaTiO3 bioceramic scaffolds may have possible application in treating tumor-induced bone defects. Abstract: For therapy of tumor-induced bone defects, functional biomaterials with tumor therapy and bone regeneration are of great importance. In this study, 3D printing of calcium titanate (CaTiO3 ) bioceramic scaffolds was prepared for the therapy of tumor-induced bone defects. The digital laser processing (DLP) based 3D printing technology was applied to prepared CaTiO3 bioceramic scaffolds. It was found that the color of CaTiO3 (CaTi) scaffolds was deeper with the sintering temperature rising. Interestingly, CaTi scaffolds with pink color were found with optimal compressive strength (13.44 ± 0.99 MPa) and satisfactory photothermal property when exposed to NIR laser. The temperature of pink CaTi scaffolds could be over 70 ℃ under NIR laser irradiation (1.32 W/cm 2 ). Attributing to such excellent photothermal performance, CaTi scaffolds had been used as a photothermal biomaterial for the effective therapy of the in vitro and in vivo bone tumor. Moreover, the prepared pink CaTi scaffolds possessed bone-forming in vitro and in vivo . Therefore, 3D printing of pink CaTi bioceramic scaffolds represents a promising strategy by using the bifunctional biomaterial for tumor-induced bone defect therapy. Graphical abstract: DLP-based 3D printed bifunctional calcium titanate scaffolds for the application of photothermal therapy and bone regeneration. Image, graphical abstract